Maleic anhydride-functionalized graphene nanofillers render epoxy coatings highly resistant to corrosion and microbial attack. (15th April 2020) - Chilkoor, Govinda; Sarder, Roman; Islam, Jamil; ArunKumar, K.E.; Ratnayake, Ishara; Star, Shane; Jasthi, Bharat K.; Sereda, Grigoriy; Koratkar, Nikhil; Meyyappan, M.; Gadhamshetty, Venkataramana
Abstract: Iron-based alloys that are ubiquitously used in industrialized societies are prone to corrosion which results in large maintenance and repair costs. Here we design maleic-anhydride-functionalized graphene nanofillers to enhance corrosion resistance of epoxy coating (MAGE) on mild steel surfaces, with a corrosion protection efficiency of 99.9%. A mechanochemical approach based on Diels-Alder reaction was used to synthesize graphene nanofillers and functionalize them with difunctional bisphenol A/epichlorohydrin epoxy. The MAGE coating increased corrosion resistance of steel by 9–10 orders of magnitude compared to bare metal in both abiotic (3.5% NaCl) and aggressive microbial (sulfate-reducing bacteria, SRB) environments. Compared to unfunctionalized graphene nanoplatelets, the MAGE coating offered four orders of magnitude lower corrosion resistance against planktonic SRB cells, 80% lower against sessile SRB cells, and 19-fold lower against 3.5% NaCl. The unique functional groups in maleic-anhydride-graphene adducts enabled their dispersion in epoxy coating and enhanced its mechanical properties. The high corrosion resistance of MAGE in diverse environments is attributed its outstanding ability to block the intercalation of corrosive species. Graphical abstract: Image 1